A midiatização de perspectivas feministas na “Era do streaming”: implicações sobre o consumo cultural de jovens periféricas - Lima, Evelane Mendonça (2023)
In the contemporary world, the dissemination of cultural goods that seek to appropriate feminist perspectives, presenting narratives that “empower” “diverse” female characters, has become commonplace. The youth audience has shown itself to be one of the groups that actively “receives” these products, especially from streaming platforms. From another angle, women were transformed into a strategic target of “media feminism”, so to speak. In view of this, the work aims to investigate how cinematographic and audiovisual productions, which are crossed, directly or indirectly, by feminist perspectives, are present in the cultural consumption of young students living in peripheral neighborhoods, located in Fortaleza and Maracanaú, in Ceará. . In methodological terms, a qualitative approach was adopted, guided by four investigative steps: a) bibliographical research and exploratory mapping of audiovisual productions with “feminist media approaches”; b) application of questionnaires with young students from three public schools, located on the outskirts of Fortaleza and Maracanaú; c) carrying out semi-structured interviews and life history interviews with the research interlocutors; d) film analysis of the audiovisual productions most consumed by the research subjects. Through this journey, it was possible to identify that young women have different experiences and practices of cultural consumption, which directly dialogue with their identities and social positions. When coming into contact with audiovisual products, they are able to distinguish, through a potentially critical look or a “politicized habitus”, the “feminist components” of productions that “empower” women, as well as the “sexist components” of productions that reinforce gender stereotypes. “Media feminism”, however, is not exactly a feminist expression. On the contrary, it is a product of a broader social dynamic: the mercantile and neoliberal capture of identity agendas by the entertainment industry. Certainly, consuming “empowerment” does not qualify as an effectively visionary feminist practice. However, the media, as it is strongly present in everyday interactions, is capable of influencing attitudes and worldviews. Furthermore, young women, as social agents, can critically reappropriate products that commodify the discursive perspectives of feminism.